LIETUVOS FILOSOFIJOS RAIDA 1960-2010: APIMTIS, INSTITUCIJOS, LEIDINIAI. - Kabelka, Gintaras (Problems / Problemos, 2012)
The article applies the approach of bibliometrics in order to analyze the development of Lithuanian philosophy. The object of the research was Lithuanian academic philosophical texts published during the period 1960 to 2010. The article analyzes regularities in quantitative growth of Lithuanian philosophical discourse. Since 1970 its growth rate is exponential: the total amount of philosophical texts doubles during 8-11 years periods. The article reveals the institutional structure of Lithuanian philosophy and the main changes in the field of philosophical publications after 1990. Research shows that Lithuanian philosophy since 1970 was growing exponentially (is in the phase of "youth of science"). It is concluded that restitution of independence has made a positive impact on the productivity of Lithuanian philosophy, and has facilitated institutional and publicational decentralisation.